Efficacy of levetiracetam for neonatal seizures in preterm infants - Ji Yoon Han; Chung Joon Moon; Young Ah Youn; In Kyung Sung; In Goo Lee (BMC Pediatrics, 2018)
Abstract Background Neonatal seizures remain a significant clinical problem, and therapeutic options are still not diverse with limited efficacy. Levetiracetam (LEV) is a relatively new and wide spectrum anti-seizure medication with favorable pharmacokinetics and safety profile. In the recent decades, LEV has been increasingly used for the treatment of neonatal seizures. The aim of this study was to describe the experience of using LEV as the first line anti-seizure medication for preterm infants. Methods A retrospective analysis of 37 preterm infants who were treated with LEV as the first-line anti-seizure medication was performed. Results Mean gestational age of the 37 preterm infants was 31.5 ± 1.9 weeks (range, 26 to 36+ 6 weeks). Twenty-one infants (57%) were seizure-free while given LEV at the end of the first week, and no additional anti-seizure medication was required. Loading doses of LEV ranged from 40 to 60 mg/kg (mean 56 mg/kg) and the maintenance dose ranged from 20 to 30 mg/kg (mean 23 mg/kg). No adverse effect was observed. Conclusions Levetiracetam can be a good and safe choice for treatment of neonatal seizures in preterm infants. Prospective double blind controlled studies are needed in the future.